2015
DOI: 10.1177/0149206314567778
|View full text |Cite
|
Sign up to set email alerts
|

Negative Relationships Between Self-Efficacy and Performance Can Be Adaptive: The Mediating Role of Resource Allocation

Abstract: This research speaks to the ongoing debate regarding the role of self-efficacy in self-regulation. Specifically, we argue that both positive and negative relationships between self-efficacy and resource allocation are part of an adaptive process. We present the results of two empirical studies demonstrating that a negative relationship between self-efficacy and resource allocation is not always maladaptive and, in fact, can lead to positive indirect effects on performance. In Study 1, we observed natural fluct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
55
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 63 publications
1
55
1
Order By: Relevance
“…In addition, Khezri azar, Lavasani, Malahmadi, and Amani (2010) report a direct effect of self-efficacy on mathematics outcomes. Self-efficacy influences performance because it determines the resources (time and effort) people choose to allocate to tasks (Beck & Schmidt, 2015). We could find no research examining self-efficacy in the domain of Materials Science, although we would expect a similar pattern of results to those reported by Dalgety and Coll for Chemistry (2006).…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…In addition, Khezri azar, Lavasani, Malahmadi, and Amani (2010) report a direct effect of self-efficacy on mathematics outcomes. Self-efficacy influences performance because it determines the resources (time and effort) people choose to allocate to tasks (Beck & Schmidt, 2015). We could find no research examining self-efficacy in the domain of Materials Science, although we would expect a similar pattern of results to those reported by Dalgety and Coll for Chemistry (2006).…”
Section: Introductionmentioning
confidence: 60%
“…The mechanism primarily responsible for the association between self-efficacy and performance is resource allocation (Beck & Schmidt, 2015). So, students who perceive themselves as having high levels of self-efficacy in academe (identity-level, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In control theory (Carver & Scheier, 2001;Powers, 1973), the discrepancy reduction tendency is emphasized, meaning that individuals regulate their invested effort (e.g., proactive career behaviours) to maintain a desired state (e.g., a career goal, current career track). Consistent with this prediction, several past studies have shown on an intraindividual level that higher self-efficacy is associated with decreases in task effort (e.g., Vancouver, Thompson, Tischner, & Putka, 2002;Vancouver, Thompson, & Williams, 2001), resource allocation (Beck & Schmidt, 2015), and performance levels (Shea & Howell, 2000;Vancouver et al, 2002), whereas lower self-efficacy motivates increased effort, resource allocations, and performance. Consequently, people with higher levels of control may decrease their effort in working towards eliminating goal-state discrepancies, due to their anticipation of less needed resources to reach their goals.…”
mentioning
confidence: 57%
“…First, we elucidate the shape and variability of intraindividual trajectories of career adaptability and proactive career behaviour. Third, we extend CCT by rationales from control theory (Carver & Scheier, 1990;Powers & Powers, 1973) and self-efficacy research (Bandura & Locke, 2003;Beck & Schmidt, 2015). Second, by disentangling inter-and intraindividual developments, the interdependence between the respective initial levels and changes in career adaptability and proactive career behaviour can be analysed in further detail (Duncan, Duncan, & Strycker, 2013;Preacher, 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation